Differentiation of the bacterial communities associated with Orbicella faveolata across different growth conditions and life-cycle stages - Amanda Pérez-Trejo; Ma. Leopoldina Aguirre-Macedo; Anastazia T. Banaszak; José Q. García-Maldonado (PLoS ONE, 2025)
The coral microbiome can strongly influence coral health, development, and resilience. While larval settlement is fundamental for coral restoration efforts using assisted larval propagation, post-settlement survival remains a major challenge. The study of lab-bred Orbicella faveolata settlers (LBOFS) microbiome has been proposed due to its potential role in coral adaptation processes. However, there is limited information about LBOFS bacterial communities and comparisons between different growth conditions and life-cycle stages have not been conducted. Using 16S rRNA high-throughput sequencing, we analyzed the structure and composition of LBOFS-associated bacteria and compared them to those from outplanted LBOFS and wild settlers. We also compared the microbiomes of settlers to adult colonies. The LBOFS bacterial community was composed of 4224 ASVs with the Orders Kiloniellales, Rhodobacterales, Cytophagales, Cyanobacteriales, and Flavobacteriales being the most abundant across the samples, with a rare biosphere consisting of 44.6% relative abundance. A Principal Coordinates Analysis and a PERMANOVA indicated significantly different bacterial community structures based on settler growth conditions and life-cycle stage. Linear discriminant analysis Effect Size analysis identified specific taxa whose differential abundances contributed to the observed differences. For settler growth conditions, the differences were mainly due to the Order Cyanobacteriales for LBOFS, SAR202 clade for outplanted settlers, and Microtrichales for wild samples. Statistical analysis of functional prediction showed significant differences only in nitrogen fixation for LBOFS. For life-cycle stage, LEfSe revealed that the Orders Cytophagales and Cyanobacteriales exhibited the highest differential abundances in adults and settlers, respectively. Functional prediction revealed that nitrogen fixation and oxygenic photoautotrophy were more enriched in settlers, whereas nitrate reduction and anaerobic chemoheterotrophy were more enriched in adults. This study highlighted the bacterial taxa and predicted metabolic processes that could potentially contribute to coral settler functioning, providing a valuable baseline for future research to enhance their survival rates using probiotics.